Bridge engineering handbook fundamentals - Chen, Wai-Fah; Duan, Lian (CRC Press, 2014)
Over 140 experts, 14 countries, and 89 chapters are represented in the second edition of The Bridge Engineering Handbook. This extensive collection highlights bridge engineering specimens from around the world, contains detailed information on bridge engineering, and thoroughly explains the concepts and practical applications surrounding the subject. Published in five books: Fundamentals, Superstructure Design, Substructure Design, Seismic Design, and Construction and Maintenance, this new edition provides numerous worked-out examples that give